AKSESSIBILITAS MASYARAKAT TERHADAP KELEMBAGAAN PEMBIAYAAN PERTANIAN DI PEDESAAN - ENDANG LESTARI HASTUTI; SUPADI - (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
Community’s Accessibility on Agricultural Financing Institutions in Rural Areas.Although the government has made some policies on channeling credit for rural communities,however, agribusiness agent’s accessibility on formal financing institutions was still relatively low,moreover to those in capable of. Research results in villages of West Java and West Nusa Tenggarashowed that community’s perception of the accessibility found it was difficult to be accessed to theformal financing institutions. This was due to a condition that the borrower should providecollateral of land certificate. In fact, most villagers do not have one because of expensive certificateland arrangement was relatively costly. Community’s accessibility on non-formal financinginstitutions was higher due to faster and simpler procedures. Therefore, an accurate and simplemodification of the financing institution is required. In addition, a government policy on landcertification is also badly needed.